IONIC LIQUIDS AS POTENTIAL CO-CATALYST FOR CO2 ELECTROCHEMICAL REDUCTION - Saadaldeen Mohammed, Sulafa Abdalmageed; Nisa Yahya, Wan Zaireen; Bustam, Mohamad Azmi; A.Hassan, Muzamil; Masri, Asiah Nusaibah; Md Golam Kibria (Malaysian Journal of Science, 2024)
Carbon dioxide electrochemical reduction (CO2ER) presents numerous advantages in mitigating greenhouse gas emissions by converting CO2 into value-added chemicals and can be integrated with renewable energy sources such as solar and wind. Nevertheless, establishing an electrochemically stable catalytic system that can effectively decrease the overpotential while maintaining high current density and faradaic efficiency is challenging. The precise mechanisms causing the reactions and the specific functions of the electrode with electrolytes are still not fully understood. Hence, a significant increase in attention has been paid to using ionic liquids (ILs) as electrolytes for CO2ER. This phenomenon is attributed to the unique capabilities of ILs to reduce overpotential, increase current density, and improve electrochemical stability. Therefore, this study evaluated the effect of incorporating ILs into electrolytes to comprehend the cation and anion influences on CO2ER reactions. Linear sweep voltammetry (LSV) and chronoamperometry (CA) were employed to examine the reduction peaks and current density values for different electrolytes, respectively. Consequently, a 0.1 M NBu4PF6 acetonitrile solution containing 1-ethyl-3-methylimidazolium tetrafluoroborate [EMIM][BF4] demonstrated a significantly lower onset potential of the reduction by 320 mV. A reduced CO2ER efficiency involving ILs with long alkyl chains was also observed. Meanwhile, a novel hypothesis concerning molecular orbitals for the CO2ER reaction mechanism was discussed. Overall, various performance variables (reduction stability, applied potential, and current density) of CO2ER were improved using cations with short alkyl chains, anions with high highest occupied molecular orbital (HOMO) levels, and appropriate solvation media. These findings can serve as selection criteria to aid in choosing appropriate ionic liquids for CO2 electrochemical reduction (CO2ER).